Growth and Yield of Two Mustard Varieties (Brassica Juncea L.) at Various Shading Levels - Oktaviani, Oktaviani; Gustiar, Fitra; Marlina; Budianta, Dedik; Ria, Rofiqoh Purnama (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2024)
Mustard greens are one of the vegetable commodities plants. The part used is the young leaves, which can be processed into traditional medicinal and vegetable ingredients that benefit human health. This research aims to determine the level of shade tolerance on the growth and yield of mustard plants and determine mustard varieties that are tolerant of minimum sunlight conditions. This research was carried out in experimental fields using artificial fields in June – July 2023. This research used a split-plot design with 2 factors. Tafif shade as the main plot consists of no shade 0%, 55%, 70%, and 95%. The sub-plot varieties consist of the Tosakan variety and the Kumala variety. The results of the research indicate that sunlight intensity reduction negatively impacted the growth and yield of mustard plants. However, under 55% shade conditions, there was no significant difference observed in the growth and yield of mustard plants compared to those grown without shade. The Tosakan and Kumala varieties did not show any differences in the growth or yield of mustard plants.